2017
DOI: 10.1111/pbr.12510
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mapping and candidate gene analysis for fruit epidermal structure in cucumber

Abstract: Firmness of skin is an important quality of processing cucumbers, which is a feature of the palisade epidermis in these types compared to flat epidermis in fresh cucumbers. This study was conducted to map the Pe (palisade epidermis) and analyse the candidate gene. Populations derived from the cross of two inbred lines, NCG122 with fruit flat epidermis and NCG121 with fruit palisade epidermis, were used to identify the inheritance of palisade epidermis and to map the gene involved in its development. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…This variation is likely due to multiple factors controlling epidermal cell shape, including the Pe gene on chromosome 5. Pe has been localized to a 0.23 Mb region and exhibits tight, but not unbreakable, linkage to several fruit surface related traits such as dull ( D ), uniform fruit color ( u ) and tuberculate ( Tu ), suggesting a cluster of genes modulating cucumber exocarp characteristics (Yang et al, 2014a, Yang et al, 2014b, Yang et al, 2014c; Chen et al, 2016; Zhang et al, 2017; Yang et al, 2019). The QTL for epidermal cell width identified on chromosome 5 in this study is consistent with the location of Pe .…”
Section: Discussionmentioning
confidence: 99%
“…This variation is likely due to multiple factors controlling epidermal cell shape, including the Pe gene on chromosome 5. Pe has been localized to a 0.23 Mb region and exhibits tight, but not unbreakable, linkage to several fruit surface related traits such as dull ( D ), uniform fruit color ( u ) and tuberculate ( Tu ), suggesting a cluster of genes modulating cucumber exocarp characteristics (Yang et al, 2014a, Yang et al, 2014b, Yang et al, 2014c; Chen et al, 2016; Zhang et al, 2017; Yang et al, 2019). The QTL for epidermal cell width identified on chromosome 5 in this study is consistent with the location of Pe .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a gene belonging to the BZR1-BES1 family (brassinosteroid signaling pathway gene family) was highly expressed in hermaphrodite flowers (Guo et al, 2010). Shoot tips of gynoecious cucumbers treated with gibberellic acid exhibited high expression of genes SAUR32, WRKY41, CYP450, MYB21, NAC2, NAC72, SAUR21, 1AA13, CKX1, and ETR1, as identified through transcriptome and qRT-PCR analysis (Zhang et al, 2017;Zhang et al, 2019). Pan et al (2018) performed the transcriptome analysis of apical shoots of near-isogenic lines of cucumber, which included gynoecious, monoecious, and hermaphrodite, and revealed that B-class floral homeotic genes CsPI and CsAP3 were highly expressed in monoecious lines but suppressed in gynoecious lines.…”
Section: Gene Expression Studies and Transcriptome Analysismentioning
confidence: 99%
“…Moreover, a gene belonging to the BZR1-BES1 family (brassinosteroid signaling pathway gene family) was highly expressed in hermaphrodite flowers ( Guo et al, 2010 ). Shoot tips of gynoecious cucumbers treated with gibberellic acid exhibited high expression of genes SAUR32 , WRKY41 , CYP450 , MYB21 , NAC2 , NAC72 , SAUR21 , 1AA13 , CKX1 , and ETR1 , as identified through transcriptome and qRT-PCR analysis ( Zhang et al, 2017 ; Zhang et al, 2019 ).…”
Section: Gene Expression Studies and Transcriptome Analysismentioning
confidence: 99%